Efektivitas Kerja PT Textile Boyolali : Analisis Lingkungan Kerja, Budaya Organisasi dan Motivasi - Munawaroh Munawaroh; Esti Dwi Rahmawati; Taufik Nur Muftiyanto (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to determine PT Textile Boyolali work effectiveness: analysis of work environment, organizational culture and motivation. The variables used in this research are work environment and organizational culture as independent variables, work effectiveness as the dependent variable and motivation as the intervening variable. The data used in this research is primary data with the data collection method used is a questionnaire. The data analysis technique used in this research uses smart (PLS) Partial Least Square. The results of this research show that the work environment has a positive and significant effect on work effectiveness, organizational culture has a positive and significant effect on work effectiveness, motivation has a positive and significant effect on work effectiveness, the work environment has a positive and significant effect on motivation, organizational culture has a positive and significant effect on motivation, the work environment has a positive and significant effect on work effectiveness through motivation, organizational culture has a positive and significant effect on work effectiveness through motivation.